Failure to State Reasons for the Judgment in the Criminal Case - Constantin I. Gliga (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
The purpose of the criminal proceedings is to establish the facts that constitute offenses so that any person who has committed an offense can be held accountable. To accomplish this purpose, the courts, based on the evidence adduced both in the prosecution phase and in the course of the trial, deliberate and issue a judgment. Thus, we can define the judgment as the final act of the trial, the synthesis of the trial, which is achieved by presenting the arguments that demonstrate the reasoning that led the judge to adopt the solution in the case and is an essential institution of any legal system. The hypothesis considered in the elaboration of this material mainly concerns the significance of a laborious reasoning of the judgments, the negative consequences of judgments that are not reasoned, and the sanctions applied by the courts of judicial review in case of such errors.